Enhanced activity of Pt-based electrocatalysts for oxygen reduction via a selective Pt deposition process - Jeon, Tae-Yeol; Pinna, Nicola; Yoo, Sung Jong; Yu, Seung-Ho; Kim, Sang-Kyung; Lim, Seongyop; Peck, Donghyun; Jung, Doo-Hwan; Sung, Yung-Eun (ELSEVIER SCIENCE SA, 2011)
Carbon-supported Pt nanoparticles with various loading of Pt are prepared by a novel seed-mediated growth method using hydroquinone (HQ) assisted selective deposition. The structural and morphological dependence of the Pt nanoparticles on the catalytic activity in oxygen reduction reaction (ORR) is investigated. The analysis of core-level X-ray photoelectron spectroscopy (XPS) and X-ray absorption fine structure (XAFS) cannot elucidate the origin of the large enhancement of the ORR activity. In contrast, electrochemical measurements of the CO-displacement charge and the concomitant CO adlayer oxidation behavior prove that the selective deposition of additional Pt contributed to the decrease of surface defects and to the increase of the onset potential for OH adsorption. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: SINGLE-CRYSTAL SURFACES; ZERO TOTAL CHARGE; BIMETALLIC COLLOIDS; STEPPED SURFACES; PLATINUM; NANOPARTICLES; CATALYSIS; PT(111); CO; QUINONES